2015
DOI: 10.1002/etc.3242
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of decamethylpentacyclosiloxane (D5): A review

Abstract: Decamethylpentacyclosiloxane (D5) is a widely used, high-production volume personal care product with an octanol-water partition coefficient (log K OW ) of 8.09. Because of D5's high K OW and widespread use, it is subject to bioaccumulation assessments in many countries. The present study provides a compilation and an in-depth, independent review of bioaccumulation studies involving D5. The findings indicate that D5 exhibits depuration rates in fish and mammals that exceed those of extremely hydrophobic, nonbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…We therefore conclude that fugacity and activity ratios of D5 are likely below 1, suggesting that D5 does not have a propensity to biomagnify in food webs. This observation is in agreement with several food web bioaccumulation field studies, which report trophic dilution of D5 in aquatic food webs and trophic magnification factors for D5 of less than 1 . Only studies in Lake Mjøsa, Norway have indicated biomagnification, as discussed in more detail in Gobas et al .…”
Section: Resultssupporting
confidence: 92%
“…We therefore conclude that fugacity and activity ratios of D5 are likely below 1, suggesting that D5 does not have a propensity to biomagnify in food webs. This observation is in agreement with several food web bioaccumulation field studies, which report trophic dilution of D5 in aquatic food webs and trophic magnification factors for D5 of less than 1 . Only studies in Lake Mjøsa, Norway have indicated biomagnification, as discussed in more detail in Gobas et al .…”
Section: Resultssupporting
confidence: 92%
“…Table S1 is a compilation of acute and chronic toxicity data of cVMS to aquatic organisms, showing a general lack of measurable toxicity up to the water solubility or sorptive capacity in sediment. 4,29,30,38 No effects have been observed with cVMS in standard 48-or 96-h acute toxicity tests. Effects were observed for D4 (reviewed by Hobson et al 59 ) in 14-and 18-d prolonged acute toxicity studies with rainbow trout (Oncorhynchus mykiss) but not sheepshead minnow (Cyprinodon variegatus), whereas no effects were observed for D5 (D6 was not tested) in any of the prolonged acute toxicity studies.…”
Section: Bioconcentration and Toxicitymentioning
confidence: 80%
“…Activities are simply the ratio of concentration to solubility or fugacity to vapor pressure, i.e., the fraction of saturation. 29,56,57 For narcotic chemicals, acute lethality generally occurs in a range of chemical activities of 0.01−0.1; therefore, the proximity to potentially toxic conditions is readily evaluated by examining the absolute and relative activities in food web samples, as has been done for D5 by Gobas et al 29 For regulatory purposes, chemical toxicities are generally expressed either as external exposure concentrations (e.g., LC 50 values) or internal concentrations in the organism (CBR values) that cause an adverse effect. For superhydrophobic chemicals, measuring and using LC 50 values is challenging, and extrapolating them to environmental conditions is difficult because of the necessarily low exposure concentrations in water and the likely low bioavailability because of sorption to organic surfaces.…”
Section: ■ Superhydrophobic Substancesmentioning
confidence: 97%
“…Similarly to K OC , K LW is lower than would be expected based on the conventional correlation assumption that K LW equals K OW (Table ) . This assumption is not valid for D5 and possibly for other classes of lipophilic substances, as discussed by Gobas et al and Seston et al . Again, it is plausible that the behavior of D5 compared with nonpolar organics having similar K OW values relates to the differing capacities of these chemicals for the various types of molecular interactions controlling their absorption by octanol and lipids .…”
Section: Step 2: Physical Chemical and Degradation Propertiesmentioning
confidence: 97%
“…The present review specifically addresses steps 1 to 4 and step 7. Gobas et al address bioaccumulation (step 5), Fairbrother et al address toxicity and risk evaluation (steps 6 and 8), and Xu et al provide a more comprehensive treatment of physical and chemical properties (step 2).…”
Section: Introductionmentioning
confidence: 99%